Suppose that a and b are the roots of the equation 4 x 2 − 3 x − 7 = 0 . What is the sum of the squares of the reciprocals of a and b ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
thank u very much for this additional solution
In the equation 4x^2 - 3x - 7=0, it can be factored as (4x-7)(x+1)=0.
solving for the roots:
4x-7=0, then the root is 7/4
x+1=0, then the other root is -1
The reciprocals of the roots are -1 and 4/7.
To find the sum of their squares:
(-1)^2+(4/7)^2=1+16/49
49/49+16/49=65/49
aaawesomeeeeeee.,,/.//...'.[']']]'eqeqqqeq
Log in to reply
ibog ka ni joriah no?????? basin apil sad si france carsido nga naibgan nimo!!!
Log in to reply
trip lang do
Log in to reply
@A Former Brilliant Member – that's my classmate!!!! ohhhhh yeahhh
Log in to reply
@Renzo Gantala – keep up the good job
Log in to reply
@A Former Brilliant Member – ila ilaha to siya haaaaaa!!!!
Log in to reply
@Renzo Gantala – no probssssssssss'''''''
@A Former Brilliant Member – zoy///// solve my problemmmmmmm[;;;]']']']']'/.;[;[565616111jgsw
Wowwww... Easy... Chicken for you... hahaha
Problem Loading...
Note Loading...
Set Loading...
By Vieta's, a + b = 4 3 and a b = − 4 7 . Then
a 2 1 + b 2 1 = ( a b ) 2 a 2 + b 2 = ( a b ) 2 ( a + b ) 2 − 2 a b = ( 4 7 ) 2 ( 4 3 ) 2 − 2 × ( − 4 7 ) = 1 6 4 9 1 6 9 + 2 7 = 1 6 4 9 1 6 9 + 1 6 5 6 = 4 9 6 5 .